Chelating Effect of Water Extract of Mangifera foetida L. Leaf in Serum of Thalassemia Patient by Ex Vivo Test - Dessy Framita Sari; Erni Hernawati Purwaningsih; Desak Gede Budi Krisnamurti (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2012)
Thalassemia is a genetic disorder, which is caused by the diminshed synthesis of globin polypeptide chains. In Indonesia, 3-5% of cases are beta-thalassemia and 2.6 to 11% are alpha-thalassemia. Regular blood transfusion is neede but iron overload is the consequence. That's why Deferoxamine is used as a chelating agent which function is bind iron and excrete them. Unfortunately, Deferoxamine needs high cost with high side effects. Therefore, an alternative natural medicine is required, that is mangiferin derived from aqueous extract of Mangifera foetida L. leaf. The aim of this research is to utilize the natural substance as a chelating agent of feritin in thalassemia patient's serum. This was an experimental study, which used serum of patient with thalassemia. One Way ANOVA statistical test proved that the aqueous ectract of Mangifera foetida L. dose of 0.375 mg and 0.75 mg has a chelating effect compared with negative control (p=0.005). However, when subsequently tested with post hoc, 0.375 mg extract doesn't show a chelating effect compared with mangiferin (p=0.018). In the other hand, 0.75 mg extract has shown a chelating effect but not as good as mangiferin (p=0.259). It is consiered that the low doses of extract and a possibility that the extract doesn't bind the iron directly are the facttors which influence the result. That's why manfigerin still has better effectiveness in binding iron compared with aqueous extract of Mangifera foetida L. leaf dose of 0.375 mg and 0.75 mg.